A Case Report of Multidisciplinary Management of a Patient with Schimke Immuno-Osseous Dysplasia - DING Juan; WANG Wei; XIAO Juan; ZHANG Yan; ZHU Huijuan; ZHANG Wen; GAO Peng; CHEN Limeng; LYU Wei; ZOU Xuan; ZHAO Xiaoyi; SONG Hongmei; et al. (罕见病研究)
Schimke immuno-osseous dysplasia (SIOD)caused by SMARCAL1 gene mutations is a rare genetic disorder characterized by multi-system involvement, including T-cell dysfunction, skeletal dysplasia, disproportionate short stature, nephrotic syndrome, and kidney failure. This multidisciplinary consultation involved a 9-year-old boy with intrauterine growth retardation, presenting with short stature, T-cell lymphopenia, proteinuria, and degenerative bone and joint disease. Treatment primarily focused on symptomatic and supportive care. Through the multidisciplinary rare disease consultation, holistic support was provided to the patient, offering comprehensive care from various specialtiesx.We also aim to use this case report to enhance clinicians′ under-standing of SIOD and improve the management and treatment of rare diseases.